PERSPEKTIF ANTROPOLOGI BUDAYA DALAM PENGEMBANGAN MODEL KONSELING MULTIKULTURAL UNTUK PENANGANAN MASALAH PENYESUAIAN SOSIAL REMAJA - Reizki Maharani; Neviyarni; Firman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
This article discusses the importance of the cultural anthropology perspective in the development of multicultural counseling models to address social adjustment issues in adolescents. Through literature studies, the article analyzes the integration of cultural anthropology in counseling, the effectiveness of multicultural approaches, and the challenges and opportunities that exist. The research results show that a deep understanding of culture is crucial in creating relevant and effective counseling interventions for adolescents from diverse backgrounds.